A Project Feasibility Study on 3E Fetal Monitors - Francisco, Kathryn; Garcia, Jinky; Salvatus, Cherrie Joy.; Tolentino, Jamie Fer. (Diliman, Quezon City College of Engineering, 1999)
he 3E Fetal Monitor is one of the many research and development projects of the IRC Power Laboratories of the EEE Department of the University of the Philippines ? College of Engineering. The research has been made possible under the advisory of Dr. Luis Sison, with funds from Philippine Council for Advance Science and Technology Research and Development. The product is a medical equipment that detects the motion and sound of the fetal heart through the use of Doppler Technology. The direct output of the application process is heart rate, which is computed with a digital signal processor and presented on a LED display. Moreover, the observation can be viewed on a strip chart recorder that comes with the main processor. Also, the uterine contractions can be monitored with the strain gauge component which can be recorded in the same way as the fetal heart rate. The 3E Monitor aims to be a more practical substitute for its more expensive imported counterparts. As elucidated in the market analysis, the target markets are those medical institutions with no fetal monitor due to its high price, and hospitals and OB-Gyne clinics with insufficient number of fetal monitor. All of which are situated in Metro Manila. The market study shows that the expected market share for the first year of operation is 17.94% of the total demand for the product. This is equal to 37 units plus one excess unit as inventory. The total marketing budget was set at P487,308.00 for the first year. This includes a massive print media campaign and formal launching of the product. The technical study provides an estimate of the projects total start up cost equal to P 17,149,728. This covers the fixed investments. Manufacturing costs, marketing costs, a 10% contingency cost and other additional start-up cost. Production planning, capacity planning, facilities design and other specs essential to support the project were also discussed in the technical study. Several alternatives were considered and the projects were also discussed in the technical study. Several alternatives were considered and evaluated by comparison of costs and accompanying qualitative factors. It was shown that it is more economical to assemble the whole unit rather than to subcontract the DSP board and assemble the remaining components. In the design of the facilities and site location, the study group prefers to buy a commercial lot with a one-story building that only needs additional renovation to suit the plant layout. To finance the project since the business will be a corporate entity it will obtain financial support from Philippine National Bank worth P5 million at a 13.5% interest rate per annum. This is 33.78% of the capital requirement. The rest of the capital will be obtained through shares of stock at P100 per share. To man the corporation, 16 employees are needed. The organization will be headed by the general manager. One production worker will be hired. He will be guided and assisted by an electrical engineer. Two managers will directly report to the general manager. They were the Production manager and Sales manager. The Social Profitability Analysis provides an overview of the benefits and disbenefits of the project to the community. Benefits include additional fund for the local and national government, job opportunities to several individuals and cash savings due to the product?s lower price and savings from importation. All in all the production of 3E Fetal monitor is definitely feasible. If all the assumptions and conditions during the course of the study prevail and remain valid within 2.94 years the project can recover all the investments and eventually prosper.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Instrumentation, Robotics and Control Laboratory (IRC); Fetal heart rate monitoring equipment industry; Fetal heart rate monitoring--Equipment and supplies; Participatory monitoring and evaluation (Project management)